1996
DOI: 10.1101/gr.6.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 4370 expressed sequence tags from a 3'-end-specific cDNA library of human skeletal muscle by DNA sequencing and filter hybridization.

Abstract: A systematic study on the mRNA species expressed in the human skeletal muscle is presented in this paper. To carry on this study, a new method has been developed for the construction of unbiased cDNA libraries specially designed for the production of ESTs corresponding to the 3'-end portion of the mRNAs. The method has been applied to human skeletal muscle, where the analysis of the transcription profile is particularly difficult for the presence of several very abundant transcripts. To detect and quantify hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 26 publications
3
36
1
Order By: Relevance
“…GPL2011). These libraries were produced using a strategy that allows the selection of a short 3 0 -end region of mRNAs 36 and the tagging of each transcript with an unique probe. Moreover, since the 3 0 -end noncoding region is the least conserved part of the genes, our microarray greatly reduces the cross-hybridization of different mRNAs derived from genes with high similarity in the coding region (e.g.…”
Section: The Human Array 20mentioning
confidence: 99%
“…GPL2011). These libraries were produced using a strategy that allows the selection of a short 3 0 -end region of mRNAs 36 and the tagging of each transcript with an unique probe. Moreover, since the 3 0 -end noncoding region is the least conserved part of the genes, our microarray greatly reduces the cross-hybridization of different mRNAs derived from genes with high similarity in the coding region (e.g.…”
Section: The Human Array 20mentioning
confidence: 99%
“…An important issue for gene identification in the postgenome era is the identification of genes expressed at low levels. The conventional EST approach, or random sequencing of clones from regular cDNA libraries, primarily identifies the genes expressed at high levels, as shown that only thousands of genes can be identified in a library by using this strategy regardless of the large-scale efforts, and most of these genes are already known (23)(24)(25). Applying the subtraction͞normalization strategy can identify more genes expressed at lower levels, many of which are novel genes (5,26).…”
Section: Genes Highly Expressed In Myeloid Progenitormentioning
confidence: 99%
“…5,6 Mapping of ESTs and STSs ESTs and STSs sequences were retrieved from public web sites: National Center for Biotechnology Information (NCBI; http:/ /www.ncbi.nlm.nih.gov/genemap98/), Whitehead Institute Center for Biomedical research (http://www-genome.wi.mit.edu/), Généthon (http://www.genethon.fr), Cooperative of Human Linkage Center (CHLC; http://www.chlc.org/) and, for chromosome 16 only sequences, Los Alamos National Laboratory (LANL; http://www-ls.lanl.gov). [9][10][11][12][13][14][15][16][17] Primer sequences, expected PCR product sizes and PCR conditions to amplify parts of these sequences were obtained from these web sites. The ESTs and STSs were PCR amplified from genomic DNA isolated from somatic human-mouse hybrid cell lines that contain a single human chromosome 16 fragment 18 and electrophoresed on sequencing gels.…”
Section: Isolation and Analysis Of Yacs And Bacsmentioning
confidence: 99%